Advancements in biomimetic nanomaterials in the activation of NFκb receptors in cancer - Aayush, (Malaysian NANO-An International Journal, 2024)
Biomimetic nanomaterials are catching up in the field of oncology with the traditional methods of treating cancer. One of the main causes of cancer is the misregulation of NF-κB receptors in the body. They are essential for the DNA transcription, cytokine synthesis and cell survival. This study includes the roles of different biomimetic particles involved in the activation of NF-kB pathway that leads to cancer. Nuclear factor-kB (NF-kB) transcription factors are involved in a variety of physiological processes, including innate and adaptive immunological responses, cell proliferation, cell death, and inflammation. It has been established that abnormal regulation of NF-kB and the signalling pathways that govern its activity play a role in cancer formation and development, as well as tolerance to chemo- and radiotherapy. Future treatment options in nanotech. for the treatment of cancer includes the conjugation of nanoparticles and antibodies in order to supress the activation of NF-kB receptor and the use of carbon-based nanomaterial like graphene.